Neutrophil-Lymphocyte Ratio (NLR) and Platelet-Lymphocyte Ratio (PLR) as neuroinflammatory biomarkers in Amyotrophic Lateral Sclerosis (ALS) progression - Santos, Kamilla de Faria (2022)
Amyotrophic Lateral Sclerosis (ALS) is a rapidly progressing multisystemic and multifactorial neurodegenerative disease that affects upper and lower motor neurons. Neuroinflammation is an important factor in neurodegeneration, the increase of immune cells in the neural tissue and degranulation of these cells causes neuronal damage and death, thus playing an important role in ALS pathophysiology. Studies have sought to use the neutrophil-lymphocyte ratio (NLR) and the platelet-lymphocyte ratio (PLR) as biomarkers of the inflammatory response indicative of diagnosis, stratification, progression and response to treatment of several diseases, including neurodegenerative. Thus, the aim of this study was to evaluate NLR and PLR as possible biomarkers in the neurodegenerative process. This retrospective cross-sectional study was carried out with 43 ALS patients selected at the Dr. Henrique Santillo Rehabilitation and Readaptation Center (CRER), Goiânia, Goiás – Brazil. Neutrophil, platelet, and lymphocyte counts were collected from the patient's most recent hemogram. Statistical analysis was performed using SPSS software, version 26. The correlation between NLR and PLR according to clinical condition showed a significant difference in these parameters during the initial phase of ALS development (p=0.01), revealing a marked inflammatory, with subsequent decline as the disease progresses (p=0.06). Furthermore, the results indicated a moderate positive linear relationship between the two variables (r=0.57; p<0.001), showing a joint increase in these parameters. Therefore, NLR and PLR are important indicators of inflammation and can be useful due to their simplicity, high reproducibility and low-cost for routine use.